Pengembangan Modul Berbantuan Aplikasi Desmos Dan Penerapannya Dalam Pembelajaran Pbm Untuk Meningkatkan Kemampuan Komunikasi Dan Representasi Matematis Siswa Kelas Ix - Muhammad Alif Syibli; Tri Dyah Prastiti; Endang Wahyuningrum (Publikasi Indonesia, 2025)
This study aims to develop a Desmos-assisted module and implement it through Problem-Based Learning (PBM) to improve the mathematical communication and representation skills of ninth-grade students. The research employed the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation by three experts resulted in an average validity score of 90.42%, indicating that the module is highly valid. Student response questionnaires yielded an average score of 4.03 out of 5, suggesting that the module is practical to use. Student improvement was measured through pretests and posttests. The average pretest scores for communication and representation skills were 66.93 and 63.41, respectively, which increased to 92.39 and 90.72 in the posttest. The N-Gain score of 0.78 indicates a high level of improvement. These results show that using the Desmos-assisted module in PBM is effective in enhancing students’ mathematical communication and representation skills. Therefore, the developed module is feasible for use in mathematics learning at the ninth-grade level.